The right and far-right in the Portuguese democracy (1974–2022) - Marchi, R.; Alves, A. A. (The Oxford handbook of Portuguese politics, 2022)
This chapter outlines the development of the Portuguese right and far-right during the democratic regime, from 1974 to 2021, in terms of political movements and parties, ideology and electoral outcomes. The first section contextualizes the Portuguese mainstream right-of-centre parties in the context of the democratic transition and later in their evolution until 1995. The following two sections deal with the Portuguese far-right in the context of the democratic transition from 1972 to 1982, and in the period of consolidated democracy, from the 1980s until the present day, with particular attention paid to the recent populist radical right party Chega, which has achieved parliamentary representation for this political segment in Portugal for the first time. The final section returns to the Portuguese mainstream right-of-centre political space to analyse the period from the mid-1990s until the present day, when the left has become dominant and the right has mostly acted as an opposition force, with some limited exceptions.